Differences Between The Kantian Reflective Judgment And The Arendtian Reflective Judgment, And Its Rescue Through Understanding - ¨Pérez Boada, Hector Fabián (2025)
Kantian teleological reflective judgment was one of the unfinished concepts of the Königsberg philosopher, but it served as a basis, within the construction of Hannah Arendt's political thought, especially in the analysis of the contemplative life that the life of the spirit recorded in her work, and where he not only delves into judgment but also about will and thinking. However, this article seeks to rescue the reflective judgment coined by Hannah Arendt and appreciate the conceptual advance that she made in this regard compared to the reflective judgment given by Immanuel Kant; Likewise, the relevance of this faculty for ourtimes, being rescued from another human faculty such as understanding.